Impact of a child's cancer disease on parents' everyday life: a longitudinal study from Sweden. (2nd January 2017) - Hovén, Emma; Grönqvist, Helena; Pöder, Ulrika; von Essen, Louise; Lindahl Norberg, Annika
Abstract: Background: A child's cancer disease may disrupt the daily life of the affected family for a long period. The aim was to describe restrictions on parents' leisure activities and work/studies during and after the child's treatment. Methods: This study used data from a cohort of mothers and fathers (n = 246) of children diagnosed with cancer. Data was collected five times from two months after diagnosis to one year after end of treatment. Reports of restrictions were evaluated over time, between mothers and fathers, and in relation to parent-reported child symptom burden (The Memorial Symptom Assessment Scale) and partial post-traumatic stress disorder (PTSD) (The PTSD Checklist-Civilian Version). Results: Two (51%) and four (45%) months after diagnosis, about half reported that their leisure activities were restricted at least some of the time. Corresponding percentages for restrictions on work/studies were 84% and 77%. One year after end of treatment, the great majority reported that their leisure activities (91%) and/or work/studies (76%) were never/seldom restricted. During treatment, more mothers than fathers reported restrictions on work/studies all/most of the time. After end of treatment, gender was only related to reports of restrictions among parents not reporting partial PTSD. More parents who reported being restricted all/most of the time also reported partial PTSD and/or a greater symptom burden for the child. Conclusion: Parents report frequent restrictions on everyday life during treatment. One year after end of treatment, parents report only a limited impact of the child's cancer on their leisure activities and work/studies. More parents who report restrictions also report partial PTSD and/or a greater child symptom burden. The effect of gender on restrictions varies depending on reports of partial PTSD. Future studies of gender differences regarding the impact of a child's cancer on parents' everyday life should thus consider mothers' and fathers' level of psychological distress.